Analysis of different combined cycles and working fluids for LNG exergy recovery during regasification. (15th September 2018) - Badami, Marco; Bruno, Juan Carlos; Coronas, Alberto; Fambri, Gabriele
Abstract: It has been estimated that the world's consumption of Liquefied Natural Gas (LNG) will increase significantly over the next 20 years, thus making exergy recovery from the regasification process a fundamental issue. When LNG is regasified in order to distribute the fuel through a pipeline network, a large amount of exergy is released. Three combined cycle schemes for energy generation have been analysed in this paper: the first one is a direct expansion cycle, combined with a Rankine cycle, the second one presents a double expansion with reheating and a recovery heat exchanger, and the last one shows two parallel Rankine cycles working under different turbine pressures. The performance of the three cycles has been compared, and the effects of using working fluids with different characteristics have been analysed in detail. Twelve working fluids were selected, according to their thermodynamic, ambient and safety proprieties. The working pressure and temperature that maximise the specific work have been found for each cycle and fluid. Highlights: Three different combined cycles for LNG exergy recovery are analysed and compared. The specific work of the cycles using different working fluids was optimised through a genetic algorithm. Seawater temperature and minimum pressure restriction strongly effect the simulation results. Different seawater temperatures lead variation from 15 to 50% of the specific work. The most suitable working fluids seems to be ethane, propane and propylene.